Energy Efficient Scheduling for Mobile Push Notifications - Acer, Utku; Mashhadi, Afra; Forlivesi, Claudio; Kawsar, Fahim (EAI Endorsed Transactions on Energy Web, 2015)
Push notifications are small and succinct messages used by mobile applications to inform users of new events and updates. These notifications are pushed to the user devices by a set of dedicated notification servers (e.g., Apple Push Notification Server, Google Cloud Messaging Server, etc.) as they arrive from the content providers of the mobile applications. However, due to their intrinsic small size and sporadic nature, the transfer of these messages is not power efficient, especially on cellular networks. To address this, we propose a network centric scheduling mechanism that delays the delivery of these messages as appropriate by sensing and predicting users’ cellular network activities. A trace based evaluation with 60 users’ cellular network logs of 30 days shows that we can reduce the energy consumption of mobile devices by 10% for an average delay of 150 seconds in notification delivery. As a network based system that does not require any modifications to user devices, scheduling push notifications opens up interesting opportunities for mobile operators to provide value added and differentiating services, especially considering the sharp rise of non-critical push notification messages.